The relations between the x-ray spectral parameters of gamma-ray bursts - Kilerci, Ece. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
Gamma-Ray Bursts (GRBs) are the most energetic explosions in the universe. They are thought to arise from massive stellar explosions or mergers of compact objects. As a result of these processes a black hole and an acretion disk is formed and their interaction produces a relativistic jet in which gamma-rays are generated. GRB afterglows in X-rays, optics, radio bands are thought to be produced by the interaction between the relativistic jet and the interstellar medium (ISM). X-ray afterglow spectra are generally t by a photoelectrically absorbed simple power law model (ASPL) that can be modeled using three parameters. These parameters are the Galactic neutral Hydrogen column density (NH), the intrinsic Hydrogen column density (NHint)and the power law photon index ({u100000}) (apart from the normalization). In this thesis the X-ray spectral parameters evolution in time and their relations in the ASPL model are studied for a selection of 28 GRBs observed by Swift XRT up to May 2008. In this way we test the e ciency of the ASPL model to adequately t the GRB X-ray afterglow spectra. In 17 bursts the ts show variations that includes a increasing NHint with time which is nonphysical. For two burst we found a very signi cant correlation between the NHint and the {u100000}, while for 9 bursts we found a hint for a correlation between the NHint and the {u100000}. Finally, for 2 burst we found a hint for anti-correlation between the NHint and the {u100000}. We conclude that the increasing NHint variation is due to a non-physical e ect induced by the tting procedure. We stress that an ASPL model, while able to adequately t the vast majority of X-ray spectra, induces a spurious relation between the NHint and the photon index. This is partially due to the limited energy range of the XRT (0.3{10 keV). We remark that the anti-correlation relations are interesting and the possible physical e ect during the early phase should be investigated.
Keywords: Gamma ray bursts.; X-rays -- Spectra.